Neoadjuvant immunotherapy for NSCLC: superior combination strategies, optimal treatment cycles, and predictive indicators from a Bayesian meta-analysis - Liu, Yubingxue; Long, Jianlin; Deng, Huan; Chen, Wen (Frontiers in Immunology, 2025)
BackgroundNeoadjuvant immune checkpoint inhibitors (ICIs) have emerged as a promising treatment strategy for resectable non-small cell lung cancer (NSCLC). However, optimal combination strategies, treatment cycles, and predictive indicators for long-term outcomes remain unclear. This study aimed to evaluate the efficacy of various neoadjuvant ICI-based therapies in resectable NSCLC, identify the optimal treatment cycles for neoadjuvant immunochemotherapy, and assess the prognostic value of pathological complete response (pCR) and major pathological response (MPR) for event-free survival (EFS).MethodsA systematic literature search was conducted in PubMed, EMBASE, Cochrane CENTRAL, and Web of Science, including studies published up to October 2024. Bayesian models were used to analyze the efficacy of different ICI-based treatment combinations, assess the impact of immunochemotherapy cycles on MPR and pCR, and examine the predictive value of MPR and pCR for EFS.ResultsData from 34 studies were included, consisting of 32 single-arm studies (reported in 26 papers) and 8 RCTs, involving 4,593 patients. Immunochemotherapy combined with anti-angiogenesis agents was the most effective treatment strategy, significantly improving both MPR and pCR. No significant improvement in efficacy was observed when the number of neoadjuvant immunochemotherapy cycles exceeded 3 cycles. Both MPR and pCR were strong predictors of EFS. MPR showed a stronger negative correlation with event risk compared to pCR, with a log (HR) of -2.110 (95% CI: -4.150, -0.071) for MPR, and a log (HR) of -1.665 (95% CI: -2.419, -0.992) for pCR.ConclusionNeoadjuvant immunochemotherapy combined with anti-angiogenesis agents appears to be a highly effective strategy for resectable NSCLC. Three cycles of neoadjuvant immunochemotherapy demonstrated optimal efficacy in this study. Both MPR and pCR are valuable prognostic indicators for EFS, with MPR showing a stronger predictive value. These findings offer important insights for optimizing treatment strategies and informing clinical decision-making in resectable NSCLC.Systematic review registrationPROSPERO, identifier CRD42024592346.